The Influence of Content Marketing, Online Customer Reviews, and Empathy on Purchase Decision : (Case of Camille Beauty Lip Tint on TikTok) - Ritonga, Nurul Amelia Pratiwi; Soemitra, Andri; Harianto, Budi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The skincare segment of the Indonesian cosmetics industry is currently experiencing significant growth. As a result, there is intense and increasing competition within this sector. Founded in 2018, Camille Beauty is a well-regarded beauty manufacturing company that encourages consumers to purchase its products through social media marketing, particularly on platforms like TikTok. This study aims to investigate how consumers' decisions to purchase lip tints from Camille Beauty are influenced by empathy, online customer reviews, and content marketing. The sample for this quantitative study consists of 100 current students from the FEBI Management Study Program at North Sumatra State Islamic University. The sampling method employed was purposeful sampling, a non-probability technique. Data analysis was conducted using linear regression techniques, with hypothesis testing performed through t-tests and F-tests. The study's findings indicate that, for Camille Beauty lip tint purchases, empathy, content marketing, and online customer reviews all had a positive and significant impact on consumer decisions. Data were analyzed using SPSS version 25. Overall, the study confirms that empathy, content marketing, and online customer reviews have a strong and significant influence on consumer purchasing decisions for Camille Beauty lip tints.